Clinical impact of prophylactic clip closure of mucosal defects after colorectal endoscopic submucosal dissection - Harada, Hideaki; Suehiro, Satoshi; Murakami, Daisuke; Nakahara, Ryotaro; Ujihara, Tetsuro; Shimizu, Takanori; Miyama, Yasunaga; Katsuyama, Yasushi; Hayasaka, Kenji; Tounou, Shigetaka (Endoscopy International Open, 2017)
Background and study aims Endoscopic submucosal dissection (ESD) is useful for en bloc resection of superficial colorectal neoplasms to ensure accurate histologic diagnoses. However, colorectal ESD is associated with a high frequency of adverse events (AEs). We aimed to investigate the effectiveness of prophylactic clip closure (PCC) of mucosal defects for AEs after colorectal ESD.Patients and methods This study included 197 patients with 211 lesions who underwent colorectal ESD between June 2010 and August 2016. Patients who had delayed perforation, delayed bleeding, abdominal pain, or fever were defined as AEs after colorectal ESD. Complete PCC was defined as completely sutured mucosal defect using endoclips following colorectal ESD, whereas incomplete PCC was defined as the mucosal defects that did not enable PCC or were partially sutured. Clinical records were retrospectively reviewed and clinical outcomes evaluated.Results AEs occurred in 29 lesions (13.7 %), including 12 with delayed bleeding, 12 with fever, 2 with abdominal pain, 2 with fever and abdominal pain, and 1 with delayed bleeding and fever. Delayed perforation was not observed in any patient. The frequency of AEs was significantly lower in the group with complete PCC than in the group with incomplete PCC (7.3 % [9/123] vs. 22.7 % [20/88]; P < 0.001). Multivariate analysis revealed that AEs after colorectal ESD were significantly associated with tumor size and submucosal fibrosis. Subgroup analysis among the resected specimen size of < 40 mm revealed that there was no significant difference in AEs between the 2 groups (5.6 % [6/107] vs. 17.8 % [8/45]; P = 0.069). However, the frequency of fever with complete PCC was significantly lower than that with incomplete PCC (2.8 % [3/107] vs. 13.3 % [6/45]; P = 0.020).Conclusions Tumor size and submucosal fibrosis were independent risk factors for AEs after colorectal ESD. PCC may be effective in minimizing AEs after colorectal ESD, especially the frequency of fever.